If it ain’t broke, don’t fix it: differential effectiveness of emotion regulation strategies in positive versus negative contexts - Müller, Ilka; Prüßner, Luise; Holt, Daniel; Zimmermann, Verena; Schulze, Katrin; Strakosch, Ana-Maria; Barnow, Sven (PsyArXiv preprints, 2023)
Despite the importance of positive emotions for affective psychopathology, research primarily focused on negative emotion regulation. Therefore, this ecological momentary assessment study compared a broad set of emotion regulation strategies in the context of positive versus negative emotions regarding their effectiveness and associations with depressive symptoms. We analyzed data from 1,066 participants who were notified five times daily for seven consecutive days to complete a smartphone survey assessing their predominant emotions, strategies to regulate them, and subsequent emotional outcomes. - Findings show that the effectiveness of most regulation strategies depended on whether the emotional context was positive or negative. While acceptance and savoring predicted improved emotional outcomes across emotional contexts, reappraisal and problem-solving were associated with deteriorated emotional outcomes and higher depressive symptoms when regulating positive but not negative emotions. Our findings emphasize that strategies effective for regulating negative emotions may be less helpful in the context of positive emotions. Thus, context-specific interventions may be a promising approach to improve the treatment of affective disorders.
Gesehen am 13.06.2024